The Family, Medical Decision-Making, and Biotechnology Critical Reflections on Asian Moral Perspectives - Lee, Shui Chuen (Asian Studies in Bioethics and the Philosophy of Medicine ;, 2007)
East Asian medicine, biomedical research, and health care policy are framed by their own set of moral and cultural commitments. Chief among these is the influence of Confucian ideas. A rich portrayal is offered of the implications of Confucian moral and ontological understandings for medical decision-making, human embryonic stem cell research, and health care financing. What is offered is a multifaceted insight into what distinguishes East Asian bioethical reflections. This volume opens with an exploration of the Confucian recognition of the family as an entity existing in its own right and which is not reducible to its members or their interests. As the essays in this volume show, this recognition of the family supports a notion of family autonomy that contrasts with Western individualistic accounts of proper medical decision-making. There are analyses of basic concepts as well as explorations of their implications for actual medical practice. The conflicts in East Asian countries between traditional Confucian and Western bioethics are explored as well as the tension between the new reproductive technologies and traditional understandings of the family. The studies of East Asian reflections concerning the moral status of human embryos and the morality of human embryo stem cell research disclose a set of concerns quite different from those anchored in Christian and Muslim cultural perspectives. The volume closes with an exploration of how Confucian cultural resources can be drawn upon to meet the contemporary challenges of health care financing.